A novel functional C1 inhibitor activity assay in dried blood spot for diagnosis of Hereditary angioedema - Lai, Yongquan; Zhang, Guodong; Zhou, Zhiwei; Inhaber, Neil; Bernstein, Jonathan A.; Chockalingam, Priya S.; Wu, Jiang (Clinica chimica acta, 2020)
•Novel DBS method was developed for measuring C1-Inh activity in HAE patients.•Method involves reaction with C1S substrate and quantification with LC-MS/MS.•It is validated following the best practice for DBS-based diagnostic assays.•Method is capable of distinguishing healthy subjects and HAE patients.•DBS method is appropriate for HAE diagnosis in high throughput diagnostic labs. Hereditary angioedema (HAE) is a rare genetic disease caused by deficiency or dysfunction of C1 esterase inhibitor (C1-INH). Timely and accurate diagnosis is an ongoing challenge. Measurement of plasma C1-INH activity is currently the critical standard test. We describe a novel and highly robust point-of-care assay to quantify C1-INH activity in dried blood spot (DBS). C1-INH was extracted from 3 mm punches of DBS samples and incubated with excess amount of C1 esterase (C1s). The mixture was subsequentially incubated with C1s substrate, followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) quantitation of the enzyme reaction product. The assay was validated within a quantification range from 100 to 1500 mU/mL. The intra-day precision and accuracy ranged from 4.0% to 11.6% and −11.1% to −2.1%, and the inter-day precision and accuracy were 8.1–13.1% and −10.3% to 0.9%, respectively. Normal C1-INH activity (n = 103) ranged from 311 to 1090 mU/mL, whereas 23 out of 24 HAE patients exhibited C1-INH activity lower than 100 mU/mL. DBS specimen collection for measurement of functional C1-INH activity in a physician’s office is straightforward and not limited by logistic considerations and therefore, appropriate for the diagnosis of HAE in high throughput diagnostic laboratories.